Integrative lineage delimitation in rodents of the Ctenomys Corrientes group - Caraballo, Diego Alfredo (2017)
The tuco-tucos rodents (genus Ctenomys) of the Corrientes group comprise several populations that inhabit the vast area under the influence of the Iberá wetland. Lineage delimitation within the recently diverged Corrientes group is a challenging task as morphological differentiation is not conspicuous between populations. However, delimitation is crucial for evolutionary studies and conservation issues. In this study, we performed a phylogenetic analysis including cytochrome b (cyt-b) sequences from taxa that had never been studied in a comprehensive context. We integrated previously published chromosomal studies, mitochondrial phylogenies and simple sequence repeat (SSR) variability analyses, and applied a delimitation criterion over the basis of chromosomal incompatibilities and genetic exclusivity. Under this integrative approach seven independently evolving lineages were delimited in the Corrientes group: Ctenomys roigi, which conserves its former definition, Ctenomys dorbignyi and Ctenomys perrensi complex which were redefined, Sarandicito which includes the population of Paraje Sarandicito and probably a group of nearby poorly studied populations, and Iberá i, ii and iii distributed at both sides of the Iberá wetland. We discuss future perspectives to evaluate the proposed lineages and conservation issues concerning these tuco-tucos.